2021
DOI: 10.3348/kjr.2020.0099
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Prediction Models for Diagnosing Severe Aortic Stenosis Based on Aortic Valve Calcium on Cardiac Computed Tomography: Incorporation of Radiomics and Machine Learning

Abstract: Objective We aimed to develop a prediction model for diagnosing severe aortic stenosis (AS) using computed tomography (CT) radiomics features of aortic valve calcium (AVC) and machine learning (ML) algorithms. Materials and Methods We retrospectively enrolled 408 patients who underwent cardiac CT between March 2010 and August 2017 and had echocardiographic examinations (240 patients with severe AS on echocardiography [the severe AS group] and 168 patients without severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Observers segmented the AV calcium score by carefully including the region of interest in the AV leaflet and annulus and excluding calcium in the adjacent sinus of Valsalva, left ventricular outflow tract, or mitral annulus, and image noise or beam hardening artifact was excluded. From the segmented ROI, the AVC volume was measured, and an AVC score was calculated using the Agatston method ( 21 , 22 ). All CT analyses were independently performed by two radiologists blinded to clinical information, echocardiographic results, and CT analysis results of the other reader.…”
Section: Methodsmentioning
confidence: 99%
“…Observers segmented the AV calcium score by carefully including the region of interest in the AV leaflet and annulus and excluding calcium in the adjacent sinus of Valsalva, left ventricular outflow tract, or mitral annulus, and image noise or beam hardening artifact was excluded. From the segmented ROI, the AVC volume was measured, and an AVC score was calculated using the Agatston method ( 21 , 22 ). All CT analyses were independently performed by two radiologists blinded to clinical information, echocardiographic results, and CT analysis results of the other reader.…”
Section: Methodsmentioning
confidence: 99%
“…We used radiomics data on aortic valve calcium 10 and speech signal data on Parkinson's disease 11 as examples to demonstrate the application of the proposed method in this study. Due to the large dimensionality of both data sets, appropriate methods for variable selection and model classifiers are necessary.…”
Section: Applicationmentioning
confidence: 99%
“…Other parameters that determine the severity of AS include AVC attenuation, shape, symmetry, or distribution. According to a previous study, the severity of AS is linked to the degree of AVC and the location of the valve 10 . www.nature.com/scientificreports/ Radiomics refers to the extraction of high-dimensional, quantitative information from medical images in a high-throughput manner 17 .…”
Section: Radiomics Data On Aortic Valve Calcium Aortic Stenosis (As) ...mentioning
confidence: 99%
“…Recently, R. Schofield et al found that texture analysis based on cine images is of significance for the identification of the etiology of left ventricular hypertrophy (15), and Elham et al made it clear that the radiomic signatures from cine images have the potential to detect myocardial ischemia, with the best area under the curve (AUC) of 0.93 (16). On account of computing power development and process standardization, the application potential of radiomics is being constantly mined in the cardiac field, including etiology determination, diagnosis confirmation, and prognosis prediction (17)(18)(19)(20)(21). For mechanical learning, a large amount of invisible biological information included in medical images was transformed into objective and quantitative digital information (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…For mechanical learning, a large amount of invisible biological information included in medical images was transformed into objective and quantitative digital information ( 22 , 23 ). The research of Nam et al has explored the excellent diagnostic efficacy of radiomics based on calcified plaques of the aortic valve for severe aortic stenosis with the highest AUC of 0.921 ( 20 ). Previous studies had also investigated the value of texture analysis in detecting left ventricular remodeling in cardiac computed tomography and CMR T1 mapping images ( 24 , 25 ).…”
Section: Introductionmentioning
confidence: 99%